Cross-border Acquisitions and Shareholder Wealth: Evidence from China During 2000-2013 - CHANG, Zhenghao (2014)
This study investigates the shareholders’ wealth effects of cross-border acquisitions (CBAs) of Chinese and foreign acquiring companies. We identify 191 CBAs with foreign targets of Chinese acquirers and 426 CBAs with Chinese targets of foreign acquirers during the period January 2000 through December 2013.